(untitled) (The Peerian Journal, 2024)
This article explores the place and role of civil society institutions in the management of the state and society, the large-scale reforms implemented in our country, the construction of a democratic legal state and the development of a strong civil society, the role of democratic institutions in the formation and development of civil society